European Bison – a review of the reproduction problem of the hunting species - Slyvka, O. Z.; Bublei, S. V.; Delehan, I. I.; Khoyetskyy, P. B. (Forestry Education and Science: Current Challenges and Development Prospects, 2024)
Habitat transformation is associated with the degradation of faunal complexes, with the most vulnerable species facing extinction. The analysis of biological indicators of Ukrainian bison subpopulations, their inventory, and habitat studies play an important role in the study of the global population of the species. The ecosystems of the European continent have already been significantly transformed. The possibility of biological self-regulation and natural processes is very limited and likely only within a small part of Europe. It is unlikely that the preservation of a species with such significant habitat requirements, and at the same time so dependent on humans, will be achieved solely through the protection of its habitats, especially given the threats related to the preservation of its genetic diversity.